Selves in the making: a critical analysis of Barack Obama's ascendancy to power - Mhiti, Timothy (Midlands State University, 2014)
The research was designed to explore how Barack Obama constructs his self identities which enable him to get to power. This construction is reflected in his self life-writings including Dreams from My Father: A story of Race and Inheritance, The Audacity of Hope: Thoughts on Reclaiming the AmericanDream and Change We Can Believe In: Barack Obama’s Plan to RenewAmerica’s Promise. Postcolonial theories on identity construction were used for the reason that they reflect the multiple nature of individual identities. Theories of narratology were also used in a bid to highlight the politics that inheres in self life-writing. The dissertation’s thrust therefore was on how Obama deploys narrative that suits his purpose-being the President of the United States of America. It was therefore concluded that autobiography, through narrative, can play a critical role in constructing individual identities